Effect of Different Housing Systems on Growth and Welfare of Pekin Ducks - Erisir, Z.; Poyraz, O.; Onbasilar, E. E.; Erdem, E.; Kandemir, O. (Medwell Online, 2009)
The aim of this study was to investigate the effect of different housing systems on growth and welfare of Pekin ducks. A total of 420 (212 male, 208 female) one-day-old ducklings were used in this study. The ducklings were randomly divided into 4 treatment groups; 2 Intensive Systems (IS) (one without pool and the other with swimming pool) and 2 intensive systems with outside activity (IOS) (one with swimming pool and the other without pool). The IOS with swimming pool was found to influence the body weight at 6 weeks of age. Body weight at 6 weeks of age was lower in ducks reared in IOS with pool than those reared in IOS without pool. Feed consumption was the highest and also feed efficiency was the lowest in ducks reared in IS without pool. The differences between the groups in terms of values for immune response, H-L ratio, plasma corticosterone, cholesterol, glucose and triglyceride levels were not statistically significant. It is concluded that although, the most common system used for duck rearing worldwide is IS without pool, the findings of the present study indicate that IOS with swimming pool is the best system in terms of duck welfare and growth.
Keywords: Intensive housing system; outside activity; swimming pool; duck; welfare